Analisis Kesulitan Belajar Matematika Pada Materi KPK dan FPB Siswa Kelas IV SD Negeri 48 Pekanbaru - Hotlina Andriani Saragih; Siti Quratul Ain (IJoIS: Indonesian Journal of Islamic Studies, 2022)
This study aims to describe the types of students' difficulties in learning mathematics on the KPK and FPB materials and in order to describe the efforts that teachers can make in overcoming the difficulties in learning mathematics on the KPK and FPB materials. This type of research is qualitative with a case study approach. This research was conducted on fourth grade students of SD Negeri 48 Pekanbaru by taking the subjects in this study, namely high subjects, medium subjects and low subjects. Collecting research data through interviews, observation and documentation. The results of this study revealed that subjects with high abilities did not experience difficulties because they were able to learn concepts, principles and verbal problems while subjects with moderate and low abilities seemed to still have difficulty learning verbal concepts, principles and problems. Then the results of the study showed that overall teachers had made two efforts to overcome learning difficulties in fourth grade students of SD Negeri 48 Pekanbaru. This is shown by 1) the teacher develops good study attitudes and habits, 2) the teacher provides learning motivation.